High‐Performance Photodetectors Based on Effective Exciton Dissociation in Protein‐Adsorbed Multiwalled Carbon Nanotube Nanohybrids. Issue 1 (20th September 2016) - Gong, Youpin; Liu, Qingfeng; Gong, Maogang; Wang, Ti; Zeng, Guanggen; Chan, Wai‐Lun; Wu, Judy
Abstract : Biomolecule cytochrome c adsorbed to multiwalled carbon nanotubes can form interface heterojunctions for high‐efficiency exciton dissociation, photoelectron transfer and transport, in which electrons are transported along the chain of cytochrome c. The extraordinary external quantum efficiency of up to 38.2% obtained in the nanotube/cytochrome c infrared detectors illustrates that these photonic nanohybrids are promising for room temperature quantum optoelectronics.